The Impact of Uncertain Contact Location on Situation Awareness and Performance in Simulated Submarine Track Management. (November 2016) - Loft, Shayne; Morrell, Daniel B.; Ponton, Kate; Braithwaite, Janelle; Bowden, Vanessa; Huf, Samuel
Objective: The aim of these studies was to examine the extent to which uncertainty in contact location in submarine track management affected operator situation awareness (SA), workload, and performance and whether operator SA predicted unique variance in performance. Background: We extend prior research by manipulating uncertainty in contact location and by including a sample of expert track managers in a submarine combat system. Method: In Experiment 1, university students completed a track management task. In Experiment 2, expert submariners were embedded in a real submarine combat system. Uncertainty was manipulated and SA was measured using the situation present assessment method. Results: Increased uncertainty led to higher student workload and moderately impaired SA and performance, and SA predicted incremental variance in performance. Uncertainty had no effect on expert SA or the accuracy of the tactical picture compiled. On average, experts took 20 s to accept SA queries (compared with 2.18 s for students). The time taken for experts to accept SA queries, but not their subsequent response to SA queries, was positively associated with their tactical picture accuracy. Conclusion: Uncertainty can negatively impact SA, workload, and performance. Some key findings from the laboratory were replicated using experts, but the fact that experts took on average 20 s to accept SA queries presents a challenge for using SPAM in submarine control rooms. Application: Contact location is uncertain due to the use of passive sonar and hostile deception. It is essential to measure track manager SA in order to inform work design and training.